IRONI DALAM NOVEL PAPER TOWNS OLEH JOHN GREEN - RUNTUWAROUW, ANDRE STIFANO JONATHAN (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT This research which is entitled â€œIroni dalam Novel Paper Towns, Karya John Green.â€ focuses on the types of irony reflected through the characters in the novel. The writer chooses this interesting novel because this novel is one of John Greenâ€™s works which achieved the New York Times bestseller for children's books and was awarded the 2009 Edgar Award for best young adult novel. A film adapted from this novel was released on July 24, 2015. The purpose of this study is to identify, analyze, and categorize the types of Irony in this novel. Through this research, we can make a society to be realistic in developing our obsession, assumption, and thought. This research uses Edgar V. Robertsâ€™s theories from his book, Writing Themes about Literature (1964:54). He states that â€œa character in literature is an extended verbal representation of the human being specially the inner self determines that thought, speech, and behavior.â€ In addition the writer uses intrinsic approach to gain understanding about the characters and their interaction in the novel. The result of this research shows that the three tupes of irony, namely Verbal Irony, and Situational Irony, and Dramatic Irony are found in the interaction between characters in the novel. Â  Keywords : Novel, Plot, Characters, Irony, Paper Towns, John Green.